2022
DOI: 10.1007/s12072-022-10398-5
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib for the treatment of hepatocellular carcinoma—a real-world multicenter Australian cohort study

Abstract: Introduction Hepatocellular carcinoma (HCC) is a serious complication of chronic liver disease. Lenvatinib is an oral multikinase inhibitor registered to treat advanced HCC. This study evaluates the real-world experience with lenvatinib in Australia. Methods We conducted a retrospective cohort study of patients treated with lenvatinib for advanced HCC between July 2018 and November 2020 at 11 Australian tertiary care hospitals. Baseline demographic data, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In a meta-analysis addressing the use of Sorafenib in Child-Pugh B patients with advanced HCC, the median OS result was significantly worse than that of patients with a good liver function (4.6 vs. 8.8 months) [79]. Similar results have been obtained for Lenvatinib in a multicenter cohort study: 108 patients with Child-Pugh A, 27 with Child-Pugh B and 2 with Child-Pugh C were treated and the median OS was 12.5 months in those with preserved liver function vs. 5.6 months in those with decompensated liver function [80]. Regarding ICIs, Nivolumab as a monotherapy has been studied in cohort 5 of the CheckMate 040 trial, in patients with advanced HCC and Child-Pugh B: it demonstrated clinical activity (median OS of 7.6 months and 55% of response rate), with a favorable safety, thus suggesting it could be a potential treatment option for patients with Child-Pugh B liver function [81].…”
Section: How To Choose the Most Feasible Treatmentsupporting
confidence: 74%
“…In a meta-analysis addressing the use of Sorafenib in Child-Pugh B patients with advanced HCC, the median OS result was significantly worse than that of patients with a good liver function (4.6 vs. 8.8 months) [79]. Similar results have been obtained for Lenvatinib in a multicenter cohort study: 108 patients with Child-Pugh A, 27 with Child-Pugh B and 2 with Child-Pugh C were treated and the median OS was 12.5 months in those with preserved liver function vs. 5.6 months in those with decompensated liver function [80]. Regarding ICIs, Nivolumab as a monotherapy has been studied in cohort 5 of the CheckMate 040 trial, in patients with advanced HCC and Child-Pugh B: it demonstrated clinical activity (median OS of 7.6 months and 55% of response rate), with a favorable safety, thus suggesting it could be a potential treatment option for patients with Child-Pugh B liver function [81].…”
Section: How To Choose the Most Feasible Treatmentsupporting
confidence: 74%
“…Patients with uHCC treated with systematic therapy exhibit a median overall survival (OS) of only 11.8-21.2 months based on both phase III studies [3][4][5][6][7][8][9][10] and real-world studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib is a multitargeted tyrosine kinase inhibitor that inhibits the vascular endothelial growth factor receptors 1-3, fibroblast growth factor receptors 1-4, and platelet-derived growth factor receptors, RET, and KIT (5), and cause several adverse events including hypertension, diarrhea, anorexia, hand-foot skin reaction, and hypothyroidism (6). Although gastrointestinal perforation or fistula formation during lenvatinib therapy has been reported as a serious adverse effect (7,8), all reports of TEF associated with lenvatinib are for tracheoesophageal invasion of thyroid cancer (2,3). The etiology of lenvatinib-associated gastrointestinal perforation or fistula is thought to be because the inhibitory effect of lenvatinib on angiogenesis may damage the structure and function of gastrointestinal vessels (9), induce arterial thromboembolism (10), and inhibit the healing of gastrointestinal ulcers and colonic diverticulitis, which in turn may lead to perforation (11).…”
Section: Discussionmentioning
confidence: 99%